2022
DOI: 10.1039/d2em00014h
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of binary nanoparticles and humic acid on Lactuca sativa L.

Abstract: Nanoplastics and metal oxide nanoparticles as a serious threat eventually will inevitably enter the environment. Their similar particle properties likely lead to interaction and thus cause more unpredictable ecotoxicity to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…[8][9][10] Because of their small size and large specific surface area, MNPs have great potential to penetrate biological surfaces, and even cross a series of barriers to enter the blood, lymphatic system, and liver, thereby exhibiting stronger biohazard relative to larger plastic fragments and posing a serious threat to humans. 11,12 Therefore, MNPs entering agroecosystems are considered to be a new threat to food security and human health. 8,13,14 Crops are essential for human food production and ecosystem function, so the interactions of MNPs with crop plants become an emerging issue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Because of their small size and large specific surface area, MNPs have great potential to penetrate biological surfaces, and even cross a series of barriers to enter the blood, lymphatic system, and liver, thereby exhibiting stronger biohazard relative to larger plastic fragments and posing a serious threat to humans. 11,12 Therefore, MNPs entering agroecosystems are considered to be a new threat to food security and human health. 8,13,14 Crops are essential for human food production and ecosystem function, so the interactions of MNPs with crop plants become an emerging issue.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous application of Fe NP and PS NP also resulted in augmented Fe release and accumulation in plant tissues. In addition, an increase in the level of lipid peroxidation and augmented cell damage were noted in the treated plants ( Gong et al., 2022 ).…”
Section: Plants Oxidative Responsementioning
confidence: 99%
“…It was presented that NP may cause changes in plant organisms, e.g. disturbing growth, germination, genetics, physiology, morphology, photosynthesis and uptake of nutrients (described in more detail in section 2) ( Xiao et al., 2022 ; Gong et al., 2022 ; Wang et al., 2022 ; Lian et al., 2020 ; Lian et al., 2022 ). Studies on animals showed that NP and MP might influence such trait as survival, morphology, behaviour, histopathology, development and reproduction, and in consequences population dynamic ( An et al., 2021 ; Venâncio et al., 2022 ; Liu et al., 2022a ; Huang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an initial protection line against ROS accumulation and membrane lipid peroxidation, SOD primarily converts the acutely toxic cO 2 − to less toxic H 2 O 2 , 43 as evidenced by the levels of cO 2 − and H 2 O 2 in the algal cells. Previous studies have conrmed that an increase in SOD activity is associated with the activation of repair functions and is a sign of elevated antioxidant status, 44 implying that the activation of the antioxidant system enhanced the plant tolerance and resistance to binary ZnO NPs. The addition of HA induced a slightly lower SOD activity than that of binary ZnO NPs and TBBPA treatment, which further demonstrated that the regulation of HA attenuated the stress response of algal cells.…”
Section: Physiological Toxicity Of Zno Nps On Algal Cellsmentioning
confidence: 99%